The psychological as a dimension of human development. A behavioral approach - Patrón, Felipe (2019)
The present work had the purpose of pointing out and solving some of the conceptual problems related to the area of knowledge called psychological development. The first step in achieving this was to clarify whether psychological development is a sub-discipline of psychology or an area in which different disciplines converge. As objectives were reached, it was imperative to describe, in an introductory way, the strategies that have been implemented from interbehavioral psychology to solve the problems related to the definition of psychological development and, therefore, with the object of psychology study. Starting from the definition of this object, it was possible to distinguish between human development as an area of knowledge in which different disciplines converge and psychological development as an area of psychology, overcoming the confusions originated from taking them as equivalents. Finally, psychological development was defined based on functional competencies, and the relevance of replacing the concept of development with psychological becoming was discussed.